Stochastic Analysis of Financial Feasibility In Toll Road Investment - Bambang Siswanto; Ari Sandhyavitri; Manyuk Fauzi (Jurnal Mantik, 2021)
In making investment decisions for toll road infrastructure projects, financial feasibility is measured by Net Present Value (NPV) or Internal Rate of Return (IRR). This paper analyzes the financial feasibility of investing in the Pekanbaru-Dumai toll road infrastructure project through a stochastic method approach using the @Risk software application. The results of the analysis with the feasibility support from the government in the form of State Equity Participation (PMN) of 13% of construction costs with a concession period of 40 years obtained Net Present Value (NPV); minimum value of Rp (66,585.810,000); the average value of Rp. 153.573.12 million ; maximum value of IDR 1,218,854,320,000; probability of loss 5% 0 (positive). These results confirm that the Pekanbaru - Dumai toll road infrastructure project investment is financially feasible with a 95% confidence level.